Working Student and Its Impact on Learning Activities and Academic Achievements - Mardelina, Elma; Muhson, Ali (Jurnal Economia, 2017)
Abstract: Working Student and Its Impact on Learning Activities and Academic Achievements. This study is aimed to find out the impact of part-time jobs to the learning activities and academic achievements. The population of this study is students Faculty of Economics year 2013, Yogyakarta State University. The 205 samples selected using proportional random sampling approach. Questionnaire and documentation are used to collect data. This research uses MANOVA to analyze the data. The results show that there is a significant effect of part-time jobs on the learning activities and academic achievements. The working students have a lower time for learning than the non-working students. The working students’ academic achievement is lower than the non-working students. Keywords: Academic Achievements, Learning Activities, Working Student.Abstrak: Mahasiswa Bekerja dan Dampaknya Terhadap Aktivitas Belajar dan Prestasi Akademik. Penelitian bertujuan mengetahui dampak kerja part-time terhadap aktivitas belajar dan prestasi akademik mahasiswa. Populasi penelitian adalah mahasiswa S1 angkatan 2013 Fakultas Ekonomi Universitas Negeri Yogyakarta. Penelitian ini mengambil sampel sebanyak 205 responden dengan teknik propotional random sampling. Teknik pengumpulan data menggunakan kuesioner dan dokumentasi. Analisis data menggunakan metode MANOVA. Hasil penelitian menunjukkan bahwa kerja part-time memiliki pengaruh yang signifikan terhadap aktivitas belajar dan prestasi akademik. Mahasiswa yang bekerja part-time cenderung memiliki waktu yang lebih sedikit dalam aktivitas belajar dibandingkan dengan mahasiswa yang tidak bekerja. Prestasi akademik mahasiswa yang bekerja part-time juga cenderung lebih rendah dibandingkan dengan mahasiswa yang tidak bekerja. Kata Kunci : Prestasi Akademik, Aktivitas Belajar, Mahasiswa Bekerja